The Neurolytic Celiac Plexus Block Efficacy in Patients with Severe, Chronic Upper-abdominal Cancer Pain (Central Asian Journal of Medical Sciences, 2016)
Objectives: To study of the efficacy of the neurolytic celiac plexus block (NCPB) in patients with severe, chronic upper-abdominal cancer pain in reducing pain score, morphine consumption, side effects of morphine, and improving performance score. Methods: Fifty-six patients with abdominal cancer who suffered chronic, severe pain were enrolled in this study. All patients received a morphine dose of